Comparison of direct and indirect determinations of dynamic ventilation rate in a modern dairy free stall barn - Zou, Bing; Heber, Albert J; Shi, Zhengxiang; Du, Songhuai; Jin, Yaomin; Tim, Teng Teeh (International Journal of Agricultural and Biological Engineering, 2020)
Reliable estimation of the ventilation rate (VR) in intensive livestock buildings is necessary for studying building environmental control strategies and predicting indoor air quality and air emissions. As direct air exchange measurements are time-consuming and expensive, it is environmentally inefficient to measure livestock building VR continuously in practice. Hence, indirect VR estimation methods have been widely used in modelling environmental control and air emissions, and also to measure airflow in the field. The accuracy of indirect measurement methods needs to be evaluated by comparing with direct measurements. In this study, the direct and indirect methods of determining hourly and daily mean VRs were applied to a mechanically-ventilated dairy free stall barn monitored by the 24-month National Air Emissions Monitoring Study. The direct method was used to continuously monitor fan rotational speeds, and differential static pressures, coupled with periodic in-situ fan performance assessments, to calculate the VR. The indirect method consisted of estimating the VR using CO2 concentration measurements and the CO2 mass balance method. The average daily and hourly means (mean±SD) of directly measured barn ventilation rates for two years were (246±73) m3/s and (245±77) m3/s, respectively. The average daily and hourly means (mean±SD) of barn ventilation rates estimated by the CO2 mass balance method were (287±93.4) m3/s and (287±118) m3/s, respectively. Correlation analyses showed a strong correlation between the indirect CO2 mass balance method and direct measurement methods (r=0.93 for daily means and r=0.85 for hourly means).Keywords: dynamic ventilation rate, modern dairy, free stall barn, carbon dioxide, mass balance, dairy cow, direct and indirect determination, comparisonDOI: 10.25165/j.ijabe.20201306.5767Citation: Zou B, Heber A J, Shi Z X, Du S H, Jin Y, Lim T T. Comparison of direct and indirect determinations of dynamic ventilation rate in a modern dairy free stall barn. Int J Agric & Biol Eng, 2020; 13(6): 41–46.